Poznanie zmysłowe w ujęciu Fryderyka Jacobiego - Piórczyński, Józef (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2006)
In relation to material reality only direct perception as sensual perception gives unbiased, reliable cognisance. Therefore, this cognisance is irremovably receptive. A subject does not add anything of himself to the object. Thinking does not play any role in such a cognisance, because object is before any thinking. According to Jacobi sensual cognisance consists of this what is given, a certain perceived content, and of a feeling assuring the existence of what is given, e.g. a belief. These two elements are inseparable. A foundation of this approach has been prepared for Jacobi by Thomas Reid, however, it was finalised thanks to critical reference to David Hume concerning that second, not perceptive element of cognisance.